Characterization of transgenic rice expressing fusion protein Cry1Ab/Vip3A for insect resistance - Xu, Chao (Sci Rep, 2018)
Management of resistance development of insect pests is of great importance for continued utilization of Bt crop. The high-dose/refuge and pyramid (gene stacking) strategy are commonly employed to delay the evolution of insect resistance. Due to the anticipated difficulty for deployment of mandatory refuge for transgenic crops in China, where the size of farmer is quite small, stacking of genes with different modes of action is a more feasible strategy. Here we report the development of transgenic rice expressing a fusion protein of Cry1Ab and Vip3A toxin. Analysis of trypsin proteolysis suggested that the fusion protein is equivalent to the combination of Cry1Ab and Vip3A protein. The transgenic plants expressing the fusion protein were found to be highly resistant to two major rice pests, Asiatic rice borer Chilo suppressalis (Lepidoptera: Crambidae) and rice leaf folder Cnaphalocrocis medinalis (Lepidoptera: Crambidae), while their agronomic performances showed no significant difference compared to the non-transgenic recipient rice. Therefore, the transgenic rice may be utilized for rice pest control in China.